دور استخدام تقنية المعلومات والاتصالات في تطوير الأداء ألأداء الإداري من وجهة نظر إدارات مدارس التعليم الأساسي في الحلقة الثانية بسلطنة عمان - عامري, أحمد سهيل سالم (Kulliyah of Education, International Islamic University Malaysia, 2021)
The research aims to identify the role of using information and communication technology in developing administrative performance from the point of view of the departments of basic education schools in the second cycle in the Sultanate of Oman، and to identify the role of administrative performance using information and communication technology from the viewpoint of the departments of basic education schools in the second cycle schools in Dhofar Governorate، And to know the role of using information and communication technology in developing and its impact on the educational process، and to identify the obstacles facing the departments of basic education schools in dealing with information and communication technology، and to disclose the suggestions that can be made to develop administrative performance and quality of service using information and communication technology، and get to know The relationship between the acceptance of the departments of basic education schools in the second cycle schools in Dhofar Governorate to use information and communication technology due to demographic variables (gender، age، educational qualification، years of experience). The importance of this study comes from the importance of using information and communication technology in various fields, and the advantages it provides and the conditions for effectiveness and efficiency for organizations of all kinds, which have taken on the nature of innovation and ease of dealing, which has a noticeable impact on various areas of life. This study relied on the descriptive analytical approach by reviewing the theoretical literature related to information and communication technology and administrative performance، and previous studies relevant to the subject of the study، while the analytical approach in this study was based on preparing a questionnaire and analyzing it using the SPSS (Statistical Package for the Social Sciences) ) And appropriate statistical tests to test study questions. The study reached the following main results: There is a statistically significant effect of the use of information and communications technology represented in (software requirements، material requirements، human requirements، communications) on administrative performance from the viewpoint of the departments of basic education schools in the second cycle schools in Dhofar Governorate، and there is an effect of Statistical indication of software requirements on administrative performance from the viewpoint of the departments of basic education schools in the second cycle schools in Dhofar Governorate، and there is also a statistically significant effect of material requirements on the administrative performance from the viewpoint of the departments of basic education schools in the second cycle schools in Dhofar Governorate، and there is a significant effect Statistics of human requirements on administrative performance from the viewpoint of the departments of basic education schools in the second cycle schools in Dhofar Governorate. There is also no statistically significant effect of communications on administrative performance from the viewpoint of the departments of basic education schools in the second cycle schools in Dhofar Governorate.